Photonic Spectrum Analyzer for Wireless Signals in the THz Range - Benedikt Leander Krause; Anuar De Jesus Fernandez Olvera; Sascha Preu (IEEE Access, 2022)
We present an ultra-broadband and inexpensive photonic spectrum analyzer (PSA) for wireless signals with a frequency coverage from the microwave range till deep into the terahertz range. The difference frequency of two continuous-wave laser diodes works as the local oscillator frequency and a photoconductive antenna downconverts a signal under test with the aid of the optical local oscillator. With this approach we achieve a frequency coverage from less than 25 GHz to more than 1.25 THz, mostly limited by the tuning range of the lasers. No component of our spectrum analyzer needs to be interchanged in order to achieve the full tuning range, which makes our spectrum analyzer a fraction of the cost of an electronic spectrum analyzer that requires several extension modules for covering a similar frequency range. The system offers a minimum resolution bandwidth of 1.2 MHz at a displayed average noise level (DANL) as low as −113.8 dBm/Hz at 100 GHz or as low as −88.2 dBm/Hz at 1050 GHz.